2020
DOI: 10.1002/jat.4084
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic‐based toxicological investigations of ethanol to human umbilical vein endothelial cells

Abstract: Ethanol has a complex effect on the cardiovascular system in humans, but the systemic effects of ethanol to endothelial cells were rarely investigated. In this study, we exposed human umbilical vein endothelial cells (HUVECs) to 5‐ or 50‐mM ethanol and performed transcriptomics to investigate the systemic effects of ethanol. While these concentrations of ethanol did not significantly affect HUVEC viability, 5‐mM ethanol significantly upregulated and downregulated 59 and 73 genes, respectively, whereas 50‐mM et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We found that high concentration of alcohol could promote the senescence of endothelial cells, and the aging endothelial cells would further affect the osteogenic differentiation of BM-MSCs, which may provide a new therapeutic target for aging osteoporosis. Previous studies found that through the inhibition of PI3K-Akt signaling pathway, high concentration of alcohol may alter many signaling pathways in HUVECs [34]. This suggests the effects of alcohol on cell proliferation, differentiation, apoptosis and migration.…”
Section: Discussionmentioning
confidence: 90%
“…We found that high concentration of alcohol could promote the senescence of endothelial cells, and the aging endothelial cells would further affect the osteogenic differentiation of BM-MSCs, which may provide a new therapeutic target for aging osteoporosis. Previous studies found that through the inhibition of PI3K-Akt signaling pathway, high concentration of alcohol may alter many signaling pathways in HUVECs [34]. This suggests the effects of alcohol on cell proliferation, differentiation, apoptosis and migration.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to T cells, CREB3L1 and CREB3L2 are also functionally involved in the transdifferentiation of hepatic stellate cells (HSCs) and impacts the progression of liver fibrosis 36,63 . Interestingly, CREB3L2 appears to be elevated upon alcohol intake, suggesting additional potential functions of CREB3L2 in alcohol metabolism and even the pathological conditions caused by alcohol abuse [64][65][66] .…”
Section: Emerging Functions Of the Creb3 Proteins In Other Contextsmentioning
confidence: 99%
“…The authors showed that ethanol changed global gene expression profiles, gene ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. At low level of ethanol treatment (5 mM), key genes involved in calcium signaling pathway (ko04020) were altered, whereas at high level of ethanol treatment (50 mM), key genes involved in PI3K‐Akt signaling pathway (ko04151) were altered (Liu et al, 2020). Cheng et al showed that zirconia NPs with or without the presence of free fatty acids (FFAs) did not significantly induce cytotoxicity or lipid accumulation in HUVECs.…”
mentioning
confidence: 99%